Design of Real-Time Control System for Nuclear Fusion High-Power DC Test Platform - HE Shiying; HUANG Liansheng; CHEN Xiaojiao; ZHANG Xiuqing; WANG Zejing; ZUO Ying; ZHANG Xinan (发电技术)
ObjectivesIn order to support the testing requirements of the international thermonuclear experimental reactor AC/DC converter system and apply to high-precision control standards for future fusion magnet power supplies, a real-time control system suitable for high-power DC test platforms was developed.MethodsChoosing the QNX real-time operating system as the core platform and combining it with reflective memory technology provided by GE company in the United States, a network architecture for real-time high-speed data exchange was built. The system was designed with multiple operation modes to cope with different testing scenarios, while implementing different levels of safety interlocking mechanisms to ensure equipment safety. This system possessed the capabilities of setting converter operating parameters, fault identification, equipment status monitoring, and millisecond-level real-time control and safety protection functions.ResultsExperimental validation has demonstrated the system’s stability and reliability in high-power environments, achieving precise control of 120 kA steady-state current and 500 kA pulse current. Furthermore, the system not only meets the basic requirements of real-time control but also ensures safe interlocking and continuous stable operation of the equipment during multi-mode operation.ConclusionsThe designed real-time control system for the high-power DC test platform achieves efficient multi-module synchronous management and fully complies with strict millisecond-level control cycle requirements.